(untitled) (Bangladesh Journal of Urology, 2025)
The use of botulinum toxin A (BTX-A) has revolutionized the treatment of non-neurogenic and neurogenic lower urinary tract dysfunction (NLUTD) as Multiple sclerosis (MS), spinal cord injury (SCI), cerebrovascular accident (CVA) and parkinsonism disease (PD) over the past three decades. Initially, botulinum toxin was utilized as a sphincteric injection to manage detrusor sphincter dyssynergia. However, it is now primarily administered as an intradetrusor injection to treat overactive bladder (OAB) and neurogenic detrusor overactivity (NDO). Its use in urology is increasingly expanding for various conditions, e.g., idiopathic OAB, Refractory OAB, Benign prostatic hyperplasia, bladder neck obstruction, Interstitial cystitis, spina bifida, neurogenic bladder, and external sphincter dyssynergia. Urodynamic studies (UDS) were conducted, and doses were adjusted based on the condition being treated. Botox injections are available in Bangladesh and have become cost-effective. At our institute, the results and patient experiences have been promising. A retrospective study conducted between 2023 and 2024 involved patients treated with Botox following diagnosis via urodynamic study. Conclusions: Outcome of BTX-A in urology depends on proper counselling and to discuss possible expected results. There is rising focus on the long-term outcomes of BTX-A for NDO management, bladder neck obstruction, refractory OAB, and reflux diseases. Bangladesh J. Urol. 2025; 28(1): 16-21